Chemical characterization and antineoplastic effect of oligosaccharides from Cabernet Franc red wine in mammary tumor model in mice - Oliveira, Natalia Mulinari Turin; dos Santos, André Eduardo; Corso, Claudia Rita; Galindo, Claudia Martins; Adami, Eliana Rezende; da Silva, Liziane Cristine Malaquias; de Lima, Lucas Trevisan França; de Santana Filho, Arquimedes Paixão; Dittrich, Rosangela Locatelli; Klassen, Giseli; de Souza Ramos, Edneia Amancio; Sassaki, Guilherme Lanzi; et al. (The Journal of Nutritional Biochemistry, 2023)
The present study characterized oligosaccharide compounds (Oligo) in Cabernet Franc red wine and investigated its antineoplastic effects against mammary tumor cells in vivo and in vitro, isolated or in combination with chemotherapy. The Oligo fraction was characterized by nuclear magnetic resonance spectroscopy and mass spectrometry. The complex mixture of Oligo showed high amounts of oligoxyloglucuronans, oligorhamnogalacturonans, oligoarabinogalactans, and oligoglucans, such as trehalose and isomaltotriose. To investigate the antineoplastic effects of Oligo, Female Swiss mice were subcutaneously inoculated with Ehrlich tumor cells and then received vehicle (distilled water, p.o.), Oligo solution (9, 35, or 70 mg/kg, p.o.), or methotrexate (1.5 mg/kg, i.p.). The treatments were administered in a conventional (21-d) or chemopreventive (42-d) protocol. Oligo reduced the growth of Ehrlich tumors in both protocols and increased the effectiveness of methotrexate in controlling tumor growth. Oligo did not reduce the viability of MCF-7, MDA-MB-231, MDA-MB-436, and HB4a human breast cells that were cultured for 48 h, showing no cytotoxicity. Overall, Oligo exerted an in vivo antineoplastic effect and modulated immune blood cells, dependent on treatment time, and was not directly cytotoxic to tumor cells. Thus, Oligo may indirectly regulate tumor cell development and may be a promising drug for cancer therapy in combination with methotrexate. [Display omitted]